On Digital Reading - Konvit, Milan; Martin Konvit, Martin (Communications - Scientific letters of the University of Zilina, 2012)
This paper examines possible relations between traditional reading and digital reading. A hypothesis that “digital reading” is more of a metaphor than reading in the traditional sense is advocated through pointing out the differences in organization of information space, linear/nonlinear text structure and required literacy. Also, new readability formula is proposed.